2017
DOI: 10.2147/ott.s118391
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-145 inhibits the activation of the mTOR signaling pathway to suppress the proliferation and invasion of invasive pituitary adenoma cells by targeting AKT3 in vivo and in vitro

Abstract: PurposeThis study was designed to explore how miR-145 regulates the mTOR signaling pathway in invasive pituitary adenoma (IPA) by targeting AKT3.MethodsA total of 71 cases of IPA tissues and 66 cases of non-IPA tissues were obtained in this study. In vitro, the IPA cells were assigned into blank control, empty plasmid, miR-145 mimic, miR-145 inhibitor, miR-145 mimic + rapamycin, miR-145 inhibitor + rapamycin and rapamycin groups. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
2
15
0
1
Order By: Relevance
“…Many studies have shown that targeting some high-frequency hub-molecules in Table 1 has achieved good results in other types of pituitary adenomas. For example, TGFβ1 is used as a novel therapeutic target to treat resistant prolactinomas (66); the microRNA-145 inhibits the activation of the mTOR signaling by targeting AKT3 to suppress the proliferation and invasion of invasive pituitary adenoma cells (67); lncRNA H19 inhibits mTORC1 by disrupting 4E-BP1/Raptor interaction in pituitary tumors (68); and MAPK Pathways act as therapeutic targets in pituitary tumors (69). Because PI3K/Akt/mTOR and ERK/MAPK signaling pathways are significantly dysregulated in NFPA, and these two essential signaling pathways are not only related to rapid proliferation and apoptosis resistance of tumor cells, but also can regulate the activities of many other pathways and then regulate tumor growth in the multiple levels.…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…Many studies have shown that targeting some high-frequency hub-molecules in Table 1 has achieved good results in other types of pituitary adenomas. For example, TGFβ1 is used as a novel therapeutic target to treat resistant prolactinomas (66); the microRNA-145 inhibits the activation of the mTOR signaling by targeting AKT3 to suppress the proliferation and invasion of invasive pituitary adenoma cells (67); lncRNA H19 inhibits mTORC1 by disrupting 4E-BP1/Raptor interaction in pituitary tumors (68); and MAPK Pathways act as therapeutic targets in pituitary tumors (69). Because PI3K/Akt/mTOR and ERK/MAPK signaling pathways are significantly dysregulated in NFPA, and these two essential signaling pathways are not only related to rapid proliferation and apoptosis resistance of tumor cells, but also can regulate the activities of many other pathways and then regulate tumor growth in the multiple levels.…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…Dual-luciferase reporter gene assays were then performed to confirm the correlation as previously described [17]. MiR-499 mimic was synthesized referring to the sequence of mature miR-499, and was cloned into the in-house pRNA-Lenti-EGFP lentivirus vector to construct miR-499 mimic plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…As a central regulator of cell growth, mTOR plays a key role in the development and aging of cells and is involved in the pathogenesis of cardiovascular diseases, endocrine diseases, metabolic disorders, and tumors [ 72 ]. Antiproliferative responses to mTOR inhibition have been reported in studies with aggressive PA in vitro and in vivo [ 73 , 74 ]. Zhou et al showed that the miR-145 expression strongly decreased while mTOR mRNA expressions significantly increased in invasive pituitary adenoma tissues compared with those in noninvasive pituitary adenoma tissues [ 74 ].…”
Section: Mirnas and Pa Therapymentioning
confidence: 99%
“…Antiproliferative responses to mTOR inhibition have been reported in studies with aggressive PA in vitro and in vivo [ 73 , 74 ]. Zhou et al showed that the miR-145 expression strongly decreased while mTOR mRNA expressions significantly increased in invasive pituitary adenoma tissues compared with those in noninvasive pituitary adenoma tissues [ 74 ]. In addition, miR-145 can not only suppress cell proliferation, migration, and invasion in invasive PA but also promote invasive PA cell apoptosis by the mTOR signaling pathway.…”
Section: Mirnas and Pa Therapymentioning
confidence: 99%